Influence of the Storage in Bottle on the Antioxidant Activities and Related Chemical Characteristics of Wine Spirits Aged with Chestnut Staves and Micro-Oxygenation - Oliveira-Alves, Sheila (2022)
Different ageing technology of wine spirits (WSs) has been investigated, but little has been published on the chemical evolution of aged WS during storage in bottle. The purpose of this study was to examine how 12 months of storage in bottle affected the evolution of antioxidant activity (DPPH, FRAP and ABTS assays), total phenolic index (TPI) and low molecular weight (LMW) compounds content of the WSs aged through alternative technology using three micro-oxygenation levels (MOX) and nitrogen control (N). Results revealed the ability of phenolic compounds from aged WSs to scavenge free radicals during storage in bottle. Among the in vitro antioxidant-activity methods, FRAP assay was the more effective to differentiate WSs according to the ageing technology. Concerning the overall influence of storage in bottle on antioxidant activity, and TPI and LMW compounds content, the higher results were obtained for the MOX modalities (O15, O30 and O60), which showed a similar evolution. In summary, this study provides innovative information, demonstrating that the differences between the aged WSs imparted throughout the ageing process (resulting from different MOX levels) were mostly retained, and only slight modifications during storage in bottle were found